2022
DOI: 10.2147/ndt.s361461
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Combined with Corticosteroids Improved the Outcome of CIDP Patients with Autoantibodies Against Paranodal Proteins

Abstract: Purpose To investigate the response of tacrolimus to chronic inflammatory demyelinating polyneuropathy (CIDP) with autoantibodies against paranodal proteins, including neurofascin-155 (NF155), contactin-1 (CNTN1) and contactin-associated protein 1 (Caspr1). Methods We retrospectively reviewed all CIDP patients who carried anti-NF155, CNTN1 and Caspr1 antibodies and were treated with tacrolimus at Tongji hospital from Jan 2018 to Apr 2021. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…This is the first Japanese case of anti‐Caspr1 antibody‐positive CIDP, and the clinical characteristics of this case were similar to those of other cases reported from Western countries, including subacute onset, distal‐predominant limb weakness, sensory ataxia, postural hand tremor, marked increased in cerebrospinal fluid protein levels, electrophysiologically multifocal demyelinating conduction disturbance, and inadequate response to transvenous immunoglobulin therapy and steroids 5,6,11,13 . Interestingly, previous studies have suggested that anti‐Caspr1 antibody‐positive CIDP is also characterized by neuropathic pain, cranial nerve involvement or respiratory failure 5,6,11,13,18–20 ; however, the present patient showed none of these. These findings indicate that the clinical signature of Caspr1‐positive cases is similar to that of other paranode antibody‐positive cases, although there are slight differences in the clinical presentation from case to case.…”
Section: Discussionsupporting
confidence: 76%
“…This is the first Japanese case of anti‐Caspr1 antibody‐positive CIDP, and the clinical characteristics of this case were similar to those of other cases reported from Western countries, including subacute onset, distal‐predominant limb weakness, sensory ataxia, postural hand tremor, marked increased in cerebrospinal fluid protein levels, electrophysiologically multifocal demyelinating conduction disturbance, and inadequate response to transvenous immunoglobulin therapy and steroids 5,6,11,13 . Interestingly, previous studies have suggested that anti‐Caspr1 antibody‐positive CIDP is also characterized by neuropathic pain, cranial nerve involvement or respiratory failure 5,6,11,13,18–20 ; however, the present patient showed none of these. These findings indicate that the clinical signature of Caspr1‐positive cases is similar to that of other paranode antibody‐positive cases, although there are slight differences in the clinical presentation from case to case.…”
Section: Discussionsupporting
confidence: 76%